2023
DOI: 10.1029/2022gl102493
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes in Hot, Dry, and Compound Hot‐Dry Extremes Over Global Land Regions

Abstract: Socio-economic and environmental impacts of hot, dry, and compound hot-dry meteorological extremes can pose a significant distress to natural and socio-economic systems worldwide (Barriopedro et al., 2011;Zscheischler et al., 2018). It is therefore of paramount importance to provide information on how these meteorological hazards may change in the future under anthropogenic climate change.Hot and dry extremes can occur concurrently (or within a time-frame of a few weeks) at a location (Bevacqua

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 54 publications
2
19
0
1
Order By: Relevance
“…In addition, our results confirm the findings in the existing literature based on GCMs (e.g. Liu et al 2021, Wu et al 2021, De Luca and Donat 2023, Tabari and Willems 2023, Tripathy et al 2023, highlighting the Mediterranean region as a hot-spot for future CHD events, which reinforce confidence in our results.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, our results confirm the findings in the existing literature based on GCMs (e.g. Liu et al 2021, Wu et al 2021, De Luca and Donat 2023, Tabari and Willems 2023, Tripathy et al 2023, highlighting the Mediterranean region as a hot-spot for future CHD events, which reinforce confidence in our results.…”
Section: Discussionsupporting
confidence: 92%
“…Liu et al 2021, Wu et al 2021, De Luca and Donat 2023, Tabari and Willems 2023, Tripathy et al 2023 or specific regions only, such as central Europe (Sedlmeier et al 2018, Zscheischler andFischer 2020). For instance, Wu et al (2021), Liu et al (2021), Tripathy et al (2023), Tabari and Willems (2023) and De Luca and Donat (2023) found that central Europe and the Mediterranean are amongst the regions showing stronger increase in frequency and intensity of CHD events through the late 21st century. They also note that under a low-emission scenario the CHD occurrences would stabilise, hence limiting the most adverse effects on the population.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, the SPEI is computed from monthly total precipitation and monthly mean of the daily maximum and minimum temperatures, the last two used to compute potential evapotranspiration following the Hargreaves (1994) approximation; SPEI therefore represents drought in terms of lack of water availability. We use the entire investigation period as a baseline for the estimation of the distribution parameters (Vicente-Serrano et al 2020, De Luca and Donat 2023), i.e. 60 years (1960-2019 for the CMIP6 MME and BEST-GPCC datasets, and 57 years for ERA5-REGEN.…”
Section: Extreme Indicesmentioning
confidence: 99%
“…However, the extent to which these models project changes in extremes and concurrently occurring extremes has not generally been used as a criterion. Additionally, previous studies have generally focused on continental or global scales whereas in-depth regional scale evaluations are still limited [24,25]. A thorough extremes-based evaluation at a regional scale can aid in the selection of GCMs for applications that require insight regarding both individual and CHD extremes for relevant adaptation studies.…”
Section: Introductionmentioning
confidence: 99%